2021
DOI: 10.3390/nursrep11010019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Self-Efficacy among Patients Undergoing Dialysis Therapy

Abstract: (1) Background: Perceived disease-related self-efficacy is considered a fundamental component of the successful self-management of chronic diseases. Prior studies have found that self-efficacy is associated with improvements in health behaviors and health status among people with chronic kidney disease (CKD). However, few studies have evaluated self-efficacy among patients undergoing dialysis. (2) Methods: This study was performed to evaluate CKD patients’ self-efficacy and to determine the factors that signif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
1
9
1
1
Order By: Relevance
“…Concerning to the occupational and education level of the studied subjects, the result of the current study showed that three-quarters of the studied patients were not working / housewife, and more than half of them had secondary / technical education (Table 1). This finding matched with the study done by Almutary et al (2021) in Saudi Arabia 190 patients undergoing dialysis to evaluate self-efficacy among patients undergoing dialysis therapy and found that more than half of them had High School / technical education and the majority were not working (27) . This may be due to differences in residence and in culture and norms between the two countries.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Concerning to the occupational and education level of the studied subjects, the result of the current study showed that three-quarters of the studied patients were not working / housewife, and more than half of them had secondary / technical education (Table 1). This finding matched with the study done by Almutary et al (2021) in Saudi Arabia 190 patients undergoing dialysis to evaluate self-efficacy among patients undergoing dialysis therapy and found that more than half of them had High School / technical education and the majority were not working (27) . This may be due to differences in residence and in culture and norms between the two countries.…”
Section: Discussionsupporting
confidence: 89%
“…Each domain consisted of five items. The AC-QoL Questionnaire consisted of 40 items that had a four-point Likert format that ranged from 0 (never), 1 (sometimes), 2 (A lot of the time), and 3 (always) for the following questionnaire items: (1-5), (17)(18), (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), ( 39,40) and 3 (never), 2 (sometimes), 1 (A lot of the time), and 0 (always) for the following questionnaire items: (6-16), 19, 37 & 38. Scoring system of the Adult Carer Quality of Life Questionnaire: -The total score was obtained by summing responses to each item of the questionnaire. Scores on the overall questionnaire had a possible range of 0 to 120 with higher scores were indicating greater quality of life.…”
mentioning
confidence: 99%
“…[7][8][9]13,31,32 However, it should be noted that there are also factors affecting the individual's self-efficacy. 10,37,39 Based on our study results, we can report that in addition to health literacy, hemodialysis patients who are older, have a low education level, live alone, and have lost their spouse, perceive themselves as less self-efficacy in the management of chronic diseases. For this reason, based on the results of our study and the evidence from the literature, we can state that CRF patients with a low level of education 10,37 , low health literacy level, advanced age 10 , no family support 37 , advanced disease 37 , and unemployed status 39 are at risk, and that risky groups should be evaluated by healthcare professionals and supported to increase their self-efficacy levels.…”
Section: Discussionmentioning
confidence: 77%
“…In the literature, the results of studies with self-efficacy assessment tools 38 developed specifically for CRF patients are available. 39,40 However, although there is no measurement tool assessing CRFspecific health literacy, it is seen thar that studies have used general health literacy assessment tools, and that the health literacy level of CRF patients is generally insufficient. 41.42 The items of the general self-efficacy scale used in this study are intended to predict certain behaviors in health management.…”
Section: Discussionmentioning
confidence: 99%
“…Багато сучасних даних вказують на вищу оцінку діалізу пацієнтами, які знаходяться на ПД, порівняно із ГД. Тому важливо покращувати інформованість та задіяність гемодалізних пацієнтів [31].…”
unclassified